2003
DOI: 10.1089/107632703768247296
|View full text |Cite
|
Sign up to set email alerts
|

Bone Formation on Tissue-Engineered Cartilage Constructsin Vivo: Effects of Chondrocyte Viability and Mechanical Loading

Abstract: Interactions between bone and cartilage formation are critical during growth and fracture healing and may influence the functional integration of osteochondral repair constructs. In this study, the ability of tissue-engineered cartilage constructs to support bone formation under controlled mechanical loading conditions was evaluated using a lapine hydraulic bone chamber model. Articular chondrocytes were seeded onto polymer disks, cultured for 4 weeks in vitro, and then transferred to empty bone chambers previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Insights into the conductive and inductive biomolecules that control EC ossification have been essential to tissue engineering strategies focusing on cartilage formation, 57,58 osteochondral defects, 59,60 and, more recently, bone regeneration (Tables 2-4). 27,43,57,58,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] While cartilage tissue engineering strategies have focused on inducing and maintaining chondrogenic phenotypes, the induction and modulation of cartilage hypertrophy is critical to the progression of EC ossification in bone regeneration designs. 9,33,34,[37][38][39][40][41][42][43]72,[77][78][79]…”
Section: Coupling In Vivo Developmental Engineering With Native Ecm Bmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9] Insights into the conductive and inductive biomolecules that control EC ossification have been essential to tissue engineering strategies focusing on cartilage formation, 57,58 osteochondral defects, 59,60 and, more recently, bone regeneration (Tables 2-4). 27,43,57,58,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] While cartilage tissue engineering strategies have focused on inducing and maintaining chondrogenic phenotypes, the induction and modulation of cartilage hypertrophy is critical to the progression of EC ossification in bone regeneration designs. 9,33,34,[37][38][39][40][41][42][43]72,[77][78][79]…”
Section: Coupling In Vivo Developmental Engineering With Native Ecm Bmentioning
confidence: 99%
“…These recent publications (Tables 2-4) have demonstrated the capacity of cartilage tissue constructs to promote EC ossification in vivo after in vitro priming with seeded BMSCs, 60,63,64,66,67,[72][73][74][75][76][103][104][105][106][107] ESCs, 27,62,67,76 ADSCs, 108 iPSCs, 109 and articular chondrocytes (ACs). 61,67,70,71,75 Most of these studies utilized a heterotopic bone formation model in immunocompromised animals to provide evidence of osteo-and chondro-conductivity and inductivity. However, more recent studies by Bahney et al, 110 van der Stok et al, 106 Harada et al, 105 and Shoji et al 108 (Table 2) showed critical-size defect regeneration in rat femurs and mice tibias via EC ossification.…”
Section: Incorporating Scbts Into the Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The model was implemented under dynamic compression considering the same ranges of level and rate of compression as the ones applied cyclically in experimental studies (Duty et al 2007;Case et al 2003). Various cases of strain-controlled dynamic compression were simulated.…”
Section: Dynamic Compressive Loading Casesmentioning
confidence: 99%
“…The model was based on the architecture and the material properties of a PLA-Glass scaffold developed by Navarro et al (2006) and characterized by Charles-Harris et al (2008) and Charles-Harris et al (2007). Reconstructed from micro-computed tomography (micro-CT) scans, the porous scaffold was here considered filled by a biological material containing fluid, cells, and matrix and was submitted, via finite element (FE) analysis, to loading conditions reproducing cyclic compression tests performed in vivo within bone chambers (Duty et al 2007;Case et al 2003). In this study, the influence of environmental factors other than load for determining cell differentiation is ignored, and it was hypothesized that the formation of tissue with a given phenotype such as mature bone or cartilage within a porous scaffold may be controlled by a given mechanical loading condition.…”
mentioning
confidence: 99%